2010
DOI: 10.1007/s12601-010-0005-4
|View full text |Cite
|
Sign up to set email alerts
|

New records of three Paraprionospio species (Polychaeta: Spionidae) from Korean waters

Abstract: The spionid polychaete Paraprionospio pinnata (Ehlers 1901) has been widely reported from Korean waters. We examined some specimens belonging to the genus Paraprionospio that had been collected from Korean waters, and identified them as Paraprionospio coora Wilson, 1990, Paraprionospio cordifolia Yokoyama, 2007 and Paraprionospio patiens Yokoyama, 2007, which are new to the fauna of Korea. The present study suggests misidentification of the specimens that have been previously reported as P. pinnata from Kore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 7 publications
1
14
1
Order By: Relevance
“…Heteromastus filfiformis (Claparede) was also dominant species at the organic enriched sediment of the Banweol tidal flat, west coast of Korea [22]. Dominant species of tidal channel of the Gapo tidal flat, Paraprionopsio patiens Yokoyama, which was recently identified from previously known as P. pinnata [19], has been found as major dominant species in Masan Bay before and after the summer hypoxia [11,23]. According to Ray, the infaunal assemblages at its early stage established on constructed intertidal mudflats at Jonesport, Maine, USA showed that some of their dominant species was composed of opportunistic species such as Streblospio benedicti (Webster), Capitella sp., Polydora ligni (Webster), and Corophium volutator (Pallas) [3].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Heteromastus filfiformis (Claparede) was also dominant species at the organic enriched sediment of the Banweol tidal flat, west coast of Korea [22]. Dominant species of tidal channel of the Gapo tidal flat, Paraprionopsio patiens Yokoyama, which was recently identified from previously known as P. pinnata [19], has been found as major dominant species in Masan Bay before and after the summer hypoxia [11,23]. According to Ray, the infaunal assemblages at its early stage established on constructed intertidal mudflats at Jonesport, Maine, USA showed that some of their dominant species was composed of opportunistic species such as Streblospio benedicti (Webster), Capitella sp., Polydora ligni (Webster), and Corophium volutator (Pallas) [3].…”
Section: Discussionmentioning
confidence: 90%
“…Paraprionospio patiens was known as occurred at only organically enriched semi-enclosed coastal areas of Korea [19]. Hediste japonica is known as a brackish species and this species was found as one of dominant species on the sandflat of Masan Bay [20].…”
Section: Discussionmentioning
confidence: 99%
“…P. cristata (It was previously identified as Paraprionospio pinnata in China and Korean, therefore, the P. pinnata reported in Chinese waters should be P. cristata) collected in Jiaozhou Bay and the Yellow Sea may be P. inaequibranchia and P. coora (Zhou et al, 2008). P. cristata has been widely reported in Korean waters (Yokoyama and Choi, 2010). P. cristata is considered an opportunistic species (Ji et al, 2022).…”
Section: Effect Of Environmental Factors On Three Species Of Polychaetesmentioning
confidence: 99%
“…All specimens retained on the sieve were fixed in 5% buffered formaldehyde with 1% Rose Bengal for further processing and identification in the laboratory. Species-level identification of the macrobenthos (where possible) was carried out under a stereomicroscope (Leica, E24W, Germany) by following the standard literature (Fauvel, 1953;Fauchald, 1977;Abbott and Dance, 1982;Subba Rao et al, 1991;Blake et al, 2009;Yokoyama and Sukumaran, 2012;Muir and Hossain, 2014;Hutchings and Kupriyanova, 2018). The World Register of Marine Species (http://www.marinespecies.org/index.php) was followed to validate the scientific names.…”
Section: Samples Collection and Laboratory Analysesmentioning
confidence: 99%